2020
DOI: 10.1002/eem2.12149
|View full text |Cite
|
Sign up to set email alerts
|

Lithium‐Doped CuO Nanosheets: Structural Transformation, Optical, and Electrical Characteristics with Enhanced Photocatalytic and Solar Cell Performance

Abstract: Energy and environmental stuff are two of the main worries for humanity, and nanoscience plays a key role in providing the solution. Huge nano‐research activities have attracted lot of attention in the current scenario. However, designing the material with enhanced optoelectronic properties remains the foremost challenge. In the present work, the Li doped CuO nanosheets are synthesized by the chemical route and examined in photovoltaics and environmental remediation applications. The crystallographic and optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…27 A g mode represents the in-phase or out-phase rotation of CuO and B g 1 , B g 2 modes are due to the bending of CuO and symmetric stretching of oxygen respectively. 28,29…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 A g mode represents the in-phase or out-phase rotation of CuO and B g 1 , B g 2 modes are due to the bending of CuO and symmetric stretching of oxygen respectively. 28,29…”
Section: Resultsmentioning
confidence: 99%
“…27 A g mode represents the in-phase or out-phase rotation of CuO and B g 1 , B g 2 modes are due to the bending of CuO and symmetric stretching of oxygen respectively. 28,29 Fig. 5 shows the Raman spectra of Mg doped CuO thin lms deposited by spray pyrolysis on glass substrate.…”
Section: Raman Analysismentioning
confidence: 99%
“…The TEM experiments showed that the morphologies of the SCuNPs‐3, Figure 3 (a–c), correspond to nanoflakes formed by the accumulation of the CuO and Cu nuclei, which aggregate to form flower‐like particles that grow in different directions with almost uniform sizes. [ 17 , 18 , 19 ] Besides, CuO and Cu nanoflakes of different sizes comprise aggregating nanorods. The width of the flakes was estimated to be 8.3 nm (Figure 3c ).…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, the arc radius of CNF/SCNF‐MS is smaller than that of CNF‐MS and SCNF‐MS, indicating the lower charge‐transfer resistance and the more efficient separation of photo‐generated charge carriers in the heterostructure for photocatalytic reactions. [ 57–59 ] Meanwhile, the lower charge‐transfer resistance of CNF‐MS and SCNF‐MS compared with CNF and SCNF (Figure , Supporting Information) proves that the higher crystallinity benefits charge‐carrier transfer process. Moreover, post treatment by NaBH 4 can further promote the charge transfer and separation of samples attributed to the introduced cyano groups that can serve as strong electron withdrawing sites.…”
Section: Resultsmentioning
confidence: 99%